The integrity of bonded amalgam restorations: a clinical evaluation after five years - Mach, Zbyněk; Regent, Jan; Staninec, Michal; Mrklas, Lubor; Setcos, James C (The Journal of the American Dental Association, 2002)
BACKGROUND: Bonded amalgam restorations have been studied extensively in vitro, but few long term clinical studies exist. The authors examined the clinical performance of bonded amalgam restorations after five years of clinical service an compared it with that of nonbonded amalgam restorations. METHODS: The authors placed 75 bonded and 62 nonbonded amalgam restorations in patients needing restorations. Most of the restorations were placed in conventional preparations; six bonded restorations were placed in nonretentive cavities. They were evaluated after a five-year period of clinical service by two trained dentists using a mirror and explorer and following modified U.S. Public Health Service criteria. RESULTS: Statistical analysis (via Fisher exact test) showed no significant differences between the two techniques when conventional preparations were used. Restorations in nonretentive preparations were successful during this period. CONCLUSIONS: Bonded and nonbonded amalgam restorations yielded similar results in conventional preparations after five years of clinical service. Bonded amalgam restorations were clinically successful in a limited number of nonretentive preparations over a five-year period. CLINICAL IMPLICATIONS: Bonded amalgam restorations can be used successfully in conventional preparations and possibly in nonretentive preparations as well, and can be expected to last at least five years.
Keywords: Dentin Sensitivity; zuby-sanace - selhání; Humans; následné studie; Dental Restoration Failure; vazba zubní; Dental Caries; Dental Marginal Adaptation; Dental Bonding; výsledek terapie; Dental Restoration, Permanent; citlivost dentinu; Follow-Up Studies; Dental Amalgam; trvalá zubní náhrada; lidé; zubní kaz; zubní marginální adaptace; zubní amalgam; Treatment Outcome